2014
DOI: 10.1051/0004-6361/201423892
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of solar photospheric bright points between Sunrise observations and MHD simulations

Abstract: Bright points (BPs) in the solar photosphere are thought to be the radiative signatures (small-scale brightness enhancements) of magnetic elements described by slender flux tubes or sheets located in the darker intergranular lanes in the solar photosphere. They contribute to the ultraviolet (UV) flux variations over the solar cycle and hence may play a role in influencing the Earth's climate. Here we aim to obtain a better insight into their properties by combining high-resolution UV and spectro-polarimetric o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 105 publications
(152 reference statements)
5
83
0
Order By: Relevance
“…Moreover, these values are consistent with the previous work of Danilovic et al (2008), who found RMS contrasts of 14.4%, 7.5%, and 7.0% in the original pixel sampling (≈10 km), the summed sampling (≈100 km) with spatial convolution, and the Hinode/SP observation used in their work, respectively. Their contrast values are slightly lower than ours because their simulation included magnetic flux, which hinders the granulation and, hence, reduces the intensity contrast (Biermann 1941;Riethmüller et al 2014). The contrast of 13.0% found in our work is also consistent with the value of 12.8% estimated by the observational approach of Mathew et al (2009), who deconvolved Hinode images using a PSF of the Hinode/SOT derived using images during the Mercury transit.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, these values are consistent with the previous work of Danilovic et al (2008), who found RMS contrasts of 14.4%, 7.5%, and 7.0% in the original pixel sampling (≈10 km), the summed sampling (≈100 km) with spatial convolution, and the Hinode/SP observation used in their work, respectively. Their contrast values are slightly lower than ours because their simulation included magnetic flux, which hinders the granulation and, hence, reduces the intensity contrast (Biermann 1941;Riethmüller et al 2014). The contrast of 13.0% found in our work is also consistent with the value of 12.8% estimated by the observational approach of Mathew et al (2009), who deconvolved Hinode images using a PSF of the Hinode/SOT derived using images during the Mercury transit.…”
Section: Discussionsupporting
confidence: 90%
“…The chosen setup was the same as that used in Riethmüller et al (2014). The calculation ran for 1 hour of solar time and we stored a snapshot containing all the physical parameters (needed for the line computation) every 30 seconds, thus producing 120 snapshots in all.…”
Section: Synthesis Of Stokes Profilesmentioning
confidence: 99%
“…This is consistent with the results of MHD simulations (Spruit 1976;Deinzer et al 1984;Riethmüller et al 2014), it is mainly an effect of the reduced opacity in the magnetic region.…”
Section: Introductionsupporting
confidence: 92%
“…Modeling the fringes by a superposition of sine curves of various amplitudes and frequencies requires little computing time when compared to more involved approaches using wavelet analysis (Rojo & Harrington 2006) or 2D pattern recognition (Casini et al 2012). Drawbacks are the danger of removing or modifying an actual signal, that is a spectral line.…”
Section: Data Description and Analysismentioning
confidence: 99%